INCOME AND COMPLIANCE TO PAY CORPORATE TAX DURING THE COVID - 19 PANDEMIC (Case Study of Sukamandi Rice Plant Research Centre) - Rismayanti Nurfitriani (Journal of Taxation Analysis and Review, 2023)
This research aims to corporate taxpayers of the Rice Plant Research Institute in Sukamandi will remain obedient to tax compliance even during the covid-19 pandemic or not during this pandemic. The subjects in this study were financial employees who served as Sub-Coordinators of Finance and Supplies of the Rice Plant Research Centre in Sukamandi. Using qualitative methods with interview techniques and data documentation that Corporate Taxpayers are obedient to paying taxes. The results of this study are that whether during the covid -19 pandemic or the absence of the covid - 19 pandemic, the corporate obligations of the Rice Plant Research Institute in Sukamandi will remain compliant with the obligation to pay taxes. Tax understanding, witnesses and audits have a positive effect on the willingness to pay corporate taxpayers.